Wingless flight: an update on ballooning in spiders and the erratical use of terms - Guerra, Carolina Beatriz (2023)
Ballooning is an aerial dispersal mechanism used by spiders, in general by small juveniles. By means of silk threads, they can travel throughout the air from short to long distances and colonize new areas. Individuals reach high positions and perform the typical tip-toeing or other behaviors such as dropping on a dragline until wind currents allow them to spread, hanging from their silk-lines. Some authors describe a behavior of short-distance aerial dispersal called rappelling, but that is not considered as ballooning. Though this phenomenon has received more attention in the last few years, some incongruity has been observed regarding the use of terminology related to ballooning. Our aim was to survey the status of aerial dispersal studies, looking for potential biases and incongruities in the use of definitions of pre-ballooning and ballooning behaviors. We used the database of research literature SCOPUS. We obtained 203 research articles, being the most used terminology ballooning (160 articles) and aerial dispersal (113 articles). 184 were experimental research articles, 9 reviews, 3 book chapters and 7 from other categories. The terms tip toe, drop on dragline and rappelling appear differentiated from ballooning in 0%, 40% and 100% of the articles containing both terms, respectively. Spider families with reports of ballooning were Actinopodidae, Araneidae, Ctenidae, Eresidae, Linyphiidae, Lycosidae, Pisauridae, Salticidae and Theridiidae. Ballooning research seems to be focused on few spider families and by a handful recognizable specialist. The need of detailed descriptions, clear definitions and common terminology of ballooning and pre-ballooning behaviors is highlighted.